(6x^2+4y^2)/(3x+7y)=3
we know that (u/v)' = (u'v-uv')/v^2, so
((12x+8yy')(3x+7y)-(6x^2+4y^2)(3+7y'))/(3x+7y)^2 = 0
36x^2 + 84xy + 24xyy' + 56y^2y'-18x^2-12y^2-42x^2y'-28y^2y' = 0
because the denominator is not zero
y'(24x+56y^2-42x^2-28y^2) = 18x^2+12y^2-36x^2-84xy
Now just divide and simplify. check on wolframalpha.com by entering
derivative (6x^2+4y^2)/(3x+7y)=3
Find the derivative of (6x^2+4y^2)/(3x+7y)=3 using implicit and quotients rule. Thank you!
2 answers
Thank you. I appreciate the help.